Weight-based optimization of sandwich shelled composite structures with a honeycomb filler - Kondratiev, Andrii; Gaidachuk, Vitaliy (Eastern-European Journal of Enterprise Technologies, 2019)
Sandwich multi-compartment shelled structures with load-bearing skins from polymer composite materials and honeycomb filler are widely used in products of different classes of equipment. This type of structures makes it possible to realize one of the highest indicators of specific strength and stiffness at minimal weight, which is one of the determining criteria of efficiency of different units. Given the fact that this structural-power configuration contains a very large number of parameters, at the change of which the weight of the product varies significantly, so far there are no generally accepted methodologies for their optimal design. The paper addresses development of the new procedure for optimization of the sandwich shelled composite structures with a honeycomb filler. Variable parameters in the procedure are thicknesses of load-bearing skin, honeycomb filler and bands of frames, geometric parameters of honeycombs; the technological mechanics of structures is also taken into consideration. The distinctive feature of the procedure is consideration in its implementation of the technological (mounting) and operational warpage of the considered shelled systems. This article analyzes the reciprocal impact of such warpages and shows the possibility to study their dependence on load parameters for the specified amplitudes of initial deflections of the technological origin. The obtained results make it possible to determine the optimal type of the reinforcement of load-bearing composite skin under the action of axial compression, transversal pressure and bending moment in the light of technological and operational deflections of the sandwich shelled system. The developed procedure and its software have implemented all major dependences of the mechanical properties of honeycombs on their geometrical parameters and the material. This made it possible to link the process of optimal designing the structures of the considered class to the technological processes of shaping the product and possibilities for a specific production according to structural materials and nomenclature of honeycombs. Implementation of the proposed procedure for optimization of the parameters of the multi-compartment sandwich shelled composite system of the type of nose fairing of a space launch vehicle revealed its efficiency expressed in reducing the weight of the optimal product. It was shown that the application of irregular hexagonal honeycombs is a fairly effective means for reducing the weight of the system